Achieving a foldable and durable OLED display with BT.2020 color space using innovative color filter structure. Issue 4 (11th April 2017) - Lee, Meng‐Ting; Wang, Cheng‐Liang; Chan, Chi‐Shun; Fu, Ching‐Chieh; Shih, Ching‐Yao; Chen, Chung‐Chia; Lin, Kuan‐Heng; Chen, Yi‐Hong; Su, Wei‐Jen; Liu, Chia‐Hsing; Ko, Chien‐Ming; Weng, Zai‐Xien; et al.
Abstract: A foldable active‐matrix organic light‐emitting diode display capable of enduring very severe folding and environmental impact was obtained using symmetric panel stacking with an innovative design of color filter structure. The display was subjected to in situ folding cycle under an ambient test condition of 60°C/90% relative humidity, and no performance degradation was found for the display and the touch function during and after the test. In addition, 95% coverage of BT.2020 color space was obtained without additional power consumption compared with that of the panel with National Television System Committee (NTSC) color space. Abstract : This paper presented a foldable AMOLED display with touch function that could achieve 95% coverage of BT.2020 color and withstand severe folding and environmental impact. The unique designs include symmetric panel stacking with a color filter structure and incorporation of new OLED emitter. These are the keys to successfully produce such a foldable device like our 5″ foldable AMOLED display.